PROSPECTS FOR THE MODERNIZATION OF INFORMATION RESOURCE CENTERS IN THE CONTEXT OF THE PRIORITIES OF THE STATE SCIENTIFIC AND TECHNICAL POLICY - Ropieva Muborak Abduganievna (Uzbekistan Open Conference, 2025)
This paper examines current issues related to the modernization of information resource centers in the context of implementing state scientific and technical policy priorities. Key aspects of their transformation from passive repositories into active elements of the national innovation infrastructure, providing full support for the research cycle, are analyzed. Particular attention is paid to international and domestic experience in integrating such centers into scientific and production activities. The article provides a detailed overview of the methodology for phased integration into the research cycle and analyzes the specific results of its testing, expressed in quantitative performance indicators. Practical aspects of implementation are considered, including the equipment used and organizational changes.
Keywords: information resource centers; modernization; scientific and technical policy; research cycle; integration; scientific infrastructure